2022
DOI: 10.3389/fmicb.2022.966735
|View full text |Cite
|
Sign up to set email alerts
|

Virome of Rhipicephalus ticks by metagenomic analysis in Guangdong, southern China

Abstract: Tick-borne viruses (TBVs) have increasingly caused a global public health concern. This study collected Rhipicephalus ticks in Guangdong, southern China to identify RNA viruses. Meta-transcriptome analysis revealed the virome in Rhipicephalus ticks, resulting in the discovery of 10 viruses, including Lihan tick virus, Brown dog tick phlebovirus 1 and 2 in the family Phenuiviridae, Mivirus and Wuhan tick virus 2 in the family Chuviridae, Wuhan tick virus 1 in the family Rhabdoviridae, bovine hepacivirus in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Our results showed that there were large numbers of viruses of the Phenuiviridae , Iflaviridae , Nairoviridae , and Chuviridae in the five species of ticks in Qingdao. Our research revealed the diversity and abundance of viruses carried by different tick species ( 26 , 27 ), which enriches the viral diversity of ticks in China.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our results showed that there were large numbers of viruses of the Phenuiviridae , Iflaviridae , Nairoviridae , and Chuviridae in the five species of ticks in Qingdao. Our research revealed the diversity and abundance of viruses carried by different tick species ( 26 , 27 ), which enriches the viral diversity of ticks in China.…”
Section: Discussionmentioning
confidence: 70%
“…The discovered viruses were classified based on nucleotide and amino acid identities (Table S3). If the nucleotide identity of a new virus species with the whole genome of the reference virus strain is less than 80% or the amino acid identity with the RNA-dependent RNA polymerase (RdRp) domain of a known virus is less than 90%, the virus is defined as a new virus ( 27 ). All new viruses were named “Qingdao tick” (QDT), followed by the names of common viruses classified by them in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Tick-associated phleboviruses identified in the pools include Brown dog tick phlebovirus 2 (BDTP2), phlebovirus Strandja, tick phlebovirus Anatolia, and Lesvos virus ( Table 1 ). Strandja and Anatolia phleboviruses were mainly reported in Rhipicephalus ticks from Bulgaria and Turkey (Emanet et al, 2019 ; Ohlendorf et al, 2019 ), while BDTP2 appears widespread, detected in China, and Trinidad and Tobago as well as the Balkans (Sameroff et al, 2019 ; Bratuleanu et al, 2022 ; Guo et al, 2022 ). Lesvos virus was originally reported from Hae.…”
Section: Resultsmentioning
confidence: 99%
“…BTV3 and tick phleboviruses appear to be a ubiquitous virus in Anatolia, having been detected in various tick species (Dinçer et al, 2017 ; Brinkmann et al, 2018 ; Emanet et al, 2019 ; Ergünay et al, 2020 ). Tick phleboviruses are also widely distributed in Asia, Europe, and America (Ohlendorf et al, 2019 ; Sameroff et al, 2019 ; Bratuleanu et al, 2022 ; Guo et al, 2022 ). As vertebrate in vivo experiments failed to propagate these viruses, they are currently considered non-virulent residents of the tick virome (Emanet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to conduct routine surveillance of tick-borne viruses. The tick viromes have been analyzed in several provinces, including Heilongjiang, Liaoning, Hebei, Henan, Yunnan and Guangdong in China [23][24][25][26][27][28], revealing a large number of novel RNA viruses of vertebrate and invertebrate hosts. These studies also suggest that the viromes are significantly affected by the tick species and geographical location.…”
Section: Introductionmentioning
confidence: 99%